Digging CACM: An archeological view of a classic. - Armour, Phillip G. (Communications of the ACM, 2008)
The article discusses content from the publication's February, 1985 issue. One column described an instance of a programmer who could log into his system while seated, but got locked out when standing up. In 1985 Grosch's Law maintained a computer's cost would rise according to the the square root of its power. If the law were true, an Xbox video game player in 2006 would cost about $93 million. Another article lamented the lack of knowledge about what kind of software tools help programmers be more productive.